Public facilities and human wellbeing in the context of Maqasid al-Shari’ah - Mohd Khazani,, Nur Amilin; Ahmad Sarkawi, Azila; Abdullah, Alias; Md. Dali, Norimah (American Scientific Publishers, 2017)
Public facilities are one of the most important land use categories in town planning. It transcends basic human needs that contribute to the overall liveability and wellbeing in its human welfare sense. The provision of public facilities somehow realizes the Maqasid al-Shariah (the objectives of Islamic law) that is to preserve the maslahah (benefits) for humankind. This study examines seven types of public facilities in Malaysia against the five essentials of Maqasid al-Shari’ah namely faith, self, intellect, posterity, and wealth. Hence it is exploratory in nature adopting the content analysis and interview with several experts from planning and Islamic background to match the public facilities provided in the plans with the Maqasid al-Shari’ah principles. The conclusive findings are that the provision of public facilities is very much conceptually related to the Maqasid al-Shari’ah. This approaches simultaneously provides an insight to the policy makers on the level of importance of the five essentials and the need to fulfill each one of them to ensure balanced provision and enjoyment of the public facilities. This also shows all those objectives of Islamic Law that should take into considerations in planning and this have been highlighted by Malaysian Government through their effort to develop the Maqasid al-Shari’ah Index to measure the “Islamicity” of the country.